Pengembangan Media Pembelajaran Berbasis Etnis Sumatera Utara - Uyuni Widiastuti; Adina Sastra Sembiring; Mukhlis Mukhlis (Universitas Negeri Surabaya, 2020)
The development of instructional media in this paper is the development of learning media used in learning Arts and Culture class X High School in Pangururan District, Samosir Regency. The learning media developed are invincible with the syllabus in class X, namely